214: THE ADDITION OF ENDOSCOPIC ULTRASOUND AND PET IMAGING HAVE MINIMAL IMPACT ON DECISION-MAKING IN EARLY OESOPHAGEAL CANCER. (23rd April 2022) - Reyhani, A; Dunn, J; Baker, C; Kelly, M; Zeki, S; Maisey, N; Lagergren, J; Gossage, J; Davies, A
Abstract: Background and aim: With the increasing use of endoscopic mucosal resection (EMR) for the staging and management of early oesophageal cancer (EOC), the value of multiple staging investigations remains clear. Methods: A single centre, ethically approved, prospective database of patients treated for EOC between 2000 and 2018 was analysed. This incorporated a transition period from oesophagectomy to endoscopic therapy as the treatment of choice for early cancers. Patients were staged with endoscopic ultrasound (EUS), Positron Emission Tomography (PET) and Computed Tomography (CT) with the accuracy and decision-making utility of these investigations assessed. Results: In total 306 patients with glandular dysplasia or early adenocarcinoma were included (EMR n = 184; Surgery n = 113; EMR and Surgery n = 23). In patients treated by EMR staging patterns were similar for all modalities with low overall accuracy (Correct staging CT 40.1%, EUS 29.6%, PET 11%; Understaging CT 54.2%, EUS 51.9%, PET 82.9%; Overstaging CT 5.6%, EUS 18.5%, PET 6.1%). Incorrect overstaging that might have changed management occurred in 10 patients (3.6%) for T staging (T2) and 14 patients (5%) for N+. Similar staging inaccuracies persisted in both the surgery alone group and in those patients treated by oesophagectomy following EMR. Lymph node disease identified following surgery was rare (n = 8) and staging accuracy for these patients was low (CT 12.5%, EUS 12.5%, PET 0%). Conclusion: In EOC, staging accuracy is low and the addition of EUS and PET change decision making in very few patients over and above standard CT. Factors predicting the need for surgery are predominantly obtained from the EMR histology rather than staging investigations. EUS and PET should only be used selectively in patients being assessed for EOC.